A Class of Sliding Mode Control for Mismatched Uncertain Systems - Ab Ghani, Mohd Ruddin (2002)
A proportional-integral sliding mode control is proposed for a system with mismatch uncertainties. The proposed controller is able to improve the chattering phenomenon. A simulation study for a numerical example is given to illustrate the effectiveness of this control design.